Pendampingan Penyusunan Administrasi Digital untuk Daftar Hadir dan Pendaftaran Siswa Berbasis Google Form di Lembaga Kursus Bahasa Inggris Zain Academy - Tri Suryanto, Bradhiansyah; Adawiyah, Robiatul; Sifaus Syauqiyah, Anggraini (Lembaga Penerbitan dan Publikasi Ilmiah, 2025)
Zain Academy as a non-formal English course institution faces obstacles in administrative management, especially related to attendance lists and student registration which are still done manually. This manual system causes various problems such as the risk of losing data, low work efficiency, and delays in recapitulating information. The purpose of this service activity is to provide practical solutions based on digital technology through assistance in using Google Form as a tool in compiling and managing digital administration. The service method used includes five main stages: identification of partner needs through field observations, design of Google Form-based digital forms, technical training for institution managers, system implementation in operational activities, and evaluation of the effectiveness of using digital forms. The solution offered is the use of two types of Google Forms, namely attendance register forms and student registration forms, which are integrated with Google Sheets and Google Drive. The results of the activity show that partners are able to operate this system independently, and have proven to be able to improve recording efficiency, data accuracy, and speed up the process of recapitulating administrative information. This activity also has a positive impact in shaping an adaptive digital work culture in the institutional environment. The conclusion of this activity is that simple technology-based assistance such as Google Form can be an effective solution for administrative digitalisation in non-formal education institutions. The limitation of this programme lies in the scope of the solution which is still limited to two aspects of administration. Therefore, it is recommended that broader system development and further training be carried out in the future, as well as replication of this model in similar institutions to strengthen digital technology-based governance in a sustainable manner.